Interaction of Small Ionic Species With Phospholipid Membranes: The Role of Metal Coordination - Le, Chanh Thi Minh; Houri, Aamd; Balage, Nimalka; Smith, Brian J.; Mechler, Adam (Frontiers in Materials, 2019)
In studies of the transfer, distribution and biochemical activity of metal ions it is typically assumed that the phospholipid bilayer acts as an inert barrier. Yet, there is mounting evidence that metal ions can influence the physical properties of membranes. Little is known of the basis of this effect. In this work the location and distribution of common metal ions: Na+, Mg2+ and Ca2+ in phospholipid membranes were studied. Computer simulations of lipid membrane segments in an aqueous environment showed that the ions penetrate the membrane headgroup zone and co-localize with the phosphate and the ester moieties. Analysis of the chemical environment of the ions in the simulations suggested that the co-localization is facilitated by coordination to the polar oxygen atoms of the phosphate and ester groups in typical coordination geometries of each ionic species, where the coordination shells are completed by water molecules. In contrast, the counterions do not penetrate the headgroup zone but form a layer over the membrane; this layer is also an effective metal exclusion zone. Importantly, the choline groups appear to be distributed almost exactly in the same plane as the phosphate, suggesting that the zwitterion dipole is preferentially horizontally aligned: this suggests that the distribution of the Cl- over the membrane surface is not a direct result of interaction with the choline groups, but rather an effect of the field emanating from the metal ion content of the membrane. Such a well defined ion distribution is expected to have a strong influence on membrane properties, in particular phase transition temperatures via increased in-plane cohesion; this was proven by calorimetry measurements using differential scanning calorimetry of suspended liposomes and quartz crystal microbalance-based measurements on supported single bilayer membranes. These findings shed a new light on the role metal ions play in stabilizing biological membranes.